Il visibile dell’invisibile - Emiliano, Macinai; Alessandra, Vezzi (Firenze University Press, 2026)
This book presents the outcomes of an educational project carried out within the courses Pedagogy of Childhood and Art and Image Education, offered as part of the Single-Cycle Degree Programme in Primary Teacher Education at the University of Florence. Throughout this experience, a pathway of in-depth theoretical study and practical teaching experimentation took shape, aimed at strengthening in the students (future teachers in early childhood and primary school) an awareness of the close connection between the artistic and the educational dimensions. More broadly, it aimed to highlight how attention to expressive language entrusted to images can reinforce and foster children's creativity, curiosity, desire to discover, and their learning.